2018
DOI: 10.1016/j.foodhyd.2017.10.017
|View full text |Cite
|
Sign up to set email alerts
|

Bionanocomposite films developed from corn starch and natural and modified nano-clays with or without added blueberry extract

Abstract: Edible and bionanocomposite films were developed by extrusion followed by thermo molding. Corn starch (Zea mays), glycerol, and several nano-clays were used as the carbohydrate polymer, plasticizer and nano-fillers, respectively. Pure blueberry (Vaccinium corymbosum) extract (BE, 100% anthocyanin), as well as natural and modified montmorillonites (Mnt) with or without BE nano-packaged within their layers were incorporated into the thermoplastic starch (TPS) matrix. Previous studies by our research group have s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
49
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(55 citation statements)
references
References 66 publications
6
49
0
Order By: Relevance
“…The lowest S a value was recorded for k0, and was 114.8 nm, and the highest for k15 was 187.7 nm. Gutierrez et al [15] showed a similar increase in the roughness of the starch film S q from 25 nm for pure TPS up to 80 nm for TPS with 4% MMT.…”
Section: Surface Morphologymentioning
confidence: 72%
“…The lowest S a value was recorded for k0, and was 114.8 nm, and the highest for k15 was 187.7 nm. Gutierrez et al [15] showed a similar increase in the roughness of the starch film S q from 25 nm for pure TPS up to 80 nm for TPS with 4% MMT.…”
Section: Surface Morphologymentioning
confidence: 72%
“…49 In addition, the UV-vis light barrier ability of starch-BBE lms was positively correlated with BBE content in the lms. Luchese et al 19 and Gutiérrez et al 50 also found the UV-vis light barrier property of anthocyanin-rich starch lms was elevated with the increase of the content of anthocyanins. Notably, a signicant reduction in the light transmittance at about 550 nm was observed for starch-BBE lms, which corresponded to the visible absorption peak of anthocyanins.…”
Section: Wvp Of Starch-bbe Lmsmentioning
confidence: 93%
“…For the systems with the different extracts, 5 wt% of the distillated water used in the matrix was replaced by the same concentration of green tea or basil extracts (they will be referred to as TPS‐T and TPS‐B, respectively). The amount of the additives has been selected considering the literature, which showed that the use of 5 wt% of different extracts in starch films led to materials with antioxidant activity and significant changes in mechanical and thermal properties . Each solution was heated with constant stirring at 96 °C for 40 min to ensure starch gelatinization .…”
Section: Methodsmentioning
confidence: 99%
“…The amount of the additives has been selected considering the literature, which showed that the use of 5 wt% of different extracts in starch films led to materials with antioxidant activity and significant changes in mechanical and thermal properties. [17,30] Each solution was heated with constant stirring at 96°C for 40 min to ensure starch gelatinization. [31] The gel was then degassed by applying vacuum for 7 min and casted on acrylic Petri dishes, which were subsequently dried at 50°C for 48 h at ambient relative humidity (RH).…”
Section: Films Preparationmentioning
confidence: 99%
See 1 more Smart Citation